Research Orientation and Development of Social Psychology’s Concept of Justice in the Era of Cloud Computing - Zhao, Yongyan; Du, Desheng (Frontiers in Psychology, 2022)
With the maturity and rapid expansion of social psychology, great progress has been made in the integration of social psychology with other disciplines. From the very beginning, social psychology is destined to have a diversified and multidisciplinary research orientation and disciplinary nature, which also makes it difficult for social psychology to be defined in a single disciplinary field and a single research method. With the rapid development of the Internet, the emergence of cloud computing technology not only facilitates the orientation of psychological research, but also promotes the emergence and development of some new psychological disciplines. Therefore, the purpose of this paper is to study the orientation of social psychology and its current development in the context of cloud computing era. This paper collects, organizes and integrates the research data of college students' view of justice from the perspective of social psychology through cloud computing technology, and uses empirical research methods to conduct in-depth research on people's view of justice in social psychology. This paper collects the data reports of college students on social justice issues through cloud computing technology to make the results more accurate. The experimental results show that nearly 70% of college students pay more attention to social justice issues. This data clearly reflects the optimistic trend of people's attention to justice issues in social psychology.